Classification Method of Small Reservoir in China Based on Risk Analysis. Issue 1 (February 2020) - Zhou, Yonghong; Bian, Xiaoqing; Chen, Yunping; Fang, Weihua
Abstract: In order to effectively manage more than 90000 small reservoirs in China, aiming at their characteristics, based on risk analysis, this article established a small reservoir dynamic risk Classification method and corresponding indexes including Safety risks factors and connecting with current specifications. in terms of the safety risk factors such as occurrence environment, structural materials, supervision and management, and accident loss. It solved the standardization and pertinence problems of small reservoir risk management in China.